2012
DOI: 10.1124/mol.112.077909
|View full text |Cite
|
Sign up to set email alerts
|

The SLCO1A2 Gene, Encoding Human Organic Anion-Transporting Polypeptide 1A2, Is Transactivated by the Vitamin D Receptor

Abstract: Organic anion-transporting polypeptide 1A2 (OATP1A2) (gene symbol, SLCO1A2) mediates cellular uptake of a wide range of endogenous substrates, as well as drugs and xenobiotics. OATP1A2 is expressed in several tissues, including apical membranes of small intestinal epithelial cells. Given its role in intestinal drug absorption, a detailed analysis of the mechanisms that regulate SLCO1A2 gene expression is potentially of great pharmacological relevance. We show here that treatment of human intestine-derived Caco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…These studies show a significant increase in the expression of OATP1A2 messenger RNA (mRNA) after 24-hour treatment with 500 nM of vitamin D 3 as well as after treatment of 50 μM of lithocholic acid (LCA), a VDR agonist, which was attenuated after small interfering RNA (siRNA)-mediated knockdown of VDR. This study also demonstrated an increase in OATP1A2 protein levels after 8 hours of treatment with vitamin D 3 (Eloranta et al, 2012). Taken together, these data strongly implicate VDR in the regulation of OATP1A2 in a manner that parallels PXR-mediated regulation in human model systems.…”
Section: Uptake Transporterssupporting
confidence: 58%
“…These studies show a significant increase in the expression of OATP1A2 messenger RNA (mRNA) after 24-hour treatment with 500 nM of vitamin D 3 as well as after treatment of 50 μM of lithocholic acid (LCA), a VDR agonist, which was attenuated after small interfering RNA (siRNA)-mediated knockdown of VDR. This study also demonstrated an increase in OATP1A2 protein levels after 8 hours of treatment with vitamin D 3 (Eloranta et al, 2012). Taken together, these data strongly implicate VDR in the regulation of OATP1A2 in a manner that parallels PXR-mediated regulation in human model systems.…”
Section: Uptake Transporterssupporting
confidence: 58%
“…We found a putative VDRE at position Ϫ1031 to Ϫ1046 from the transcription start site on the minus strand of Smad7 promoter; however, we could not identify any VDRE on the Smad3 promoter ( Fig. 2A) (33,34). The VDRE on Smad7 was the DR3 type with one consensus and one non-consensus half-site.…”
Section: Vdr Forms a Repressive Complex On The Smad7mentioning
confidence: 85%
“…(Godoy, et al, 2013; Hagenbuch & Stieger, 2013; Klaassen & Aleksunes, 2010). Lately, the vitamin D receptor VDR has been added to this list, and it has been shown to activate the expression of SLCO1A2 (Eloranta, Hiller, Juttner, & Kullak-Ublick, 2012). As ligands for nuclear receptors are also substrates for OATPs (Gui, et al, 2008), the transporters may, to some extent, control the access of nuclear receptor ligands to their own genes.…”
Section: Regulation Of Oatpsmentioning
confidence: 99%